2019
DOI: 10.1016/j.brainres.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Golgi morphology and decreased COPI function in cells with low levels of SMN

Abstract: We report here the finding of abnormal Golgi apparatus morphology in motor neuron like cells depleted of SMN as well as Golgi apparatus morphology in SMA patient fibroblasts. Rescue experiments demonstrate that this abnormality is dependent on SMN, but can also be rescued by expression of the COPI coatomer subunit alpha-COP. A motor neuron-like cell line containing an inducible alpha-COP shRNA was created to generate a parallel system to study knockdown of SMN or alpha-COP. Multiple assays of COPI-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…We believe that expression of α-COP is redistributing the low levels of SMN protein available and directing its ability to support motor neuron function. We recently showed that in motor neuron-like NSC-34 cells, SMN protein is absent from the growth cone following depletion of α-COP, indicating that α-COP expression is required for normal distribution of SMN, and echoing finding from a previous publication which reported that a portion of the SMN protein was sequestered in the trans-Golgi network following knockdown of α-COP [23,26].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We believe that expression of α-COP is redistributing the low levels of SMN protein available and directing its ability to support motor neuron function. We recently showed that in motor neuron-like NSC-34 cells, SMN protein is absent from the growth cone following depletion of α-COP, indicating that α-COP expression is required for normal distribution of SMN, and echoing finding from a previous publication which reported that a portion of the SMN protein was sequestered in the trans-Golgi network following knockdown of α-COP [23,26].…”
Section: Discussionsupporting
confidence: 67%
“…In a zebrafish model of SMA, expression of these dilysine mutants was unable to restore normal motor neuron morphology [17]. However, not all SMN function is affected by this mutation as SMN with lysines 76, 77, 82 and 83 mutated to alanine (referred to as SMN ΔΔ) was able to restore Golgi morphology to normal in SMA patient fibroblasts despite its inability to bind α-COP [23]. To determine whether the dilysine motif was required the human SMN rescue of SMA disease pathology in the 5058 mouse model, we used site-directed mutagenesis to convert either lysine 76 and 77 (Δ76), lysine 82 and 83 (Δ82) or all four lysines to alanines SMN ΔΔ.…”
Section: Lentiviral-mediated Transgenic Expression Of Dilysine Mutantmentioning
confidence: 99%
“…SMN (survival of motor neurons) proteins are ubiquitously expressed and have been involved in different functions, including snRNP transport, nuclear RNA splicing and profilin and actin-dependent axonal transport [142]. Interestingly, SMN proteins bind the coatomer subunit α-COP [143] and low levels of SMN proteins affect COPI-dependent ER-Golgi transport [144]. Fibroblasts from SMA patients have an altered Golgi, a morphology that can be rescued by over-expression of α-COP or SMN proteins [144].…”
Section: Lessons From Other Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, SMN proteins bind the coatomer subunit α-COP [143] and low levels of SMN proteins affect COPI-dependent ER-Golgi transport [144]. Fibroblasts from SMA patients have an altered Golgi, a morphology that can be rescued by over-expression of α-COP or SMN proteins [144]. Thus, Golgi alteration in SMA samples could be due to suboptimal α-COP functioning.…”
Section: Lessons From Other Neurodegenerative Diseasesmentioning
confidence: 99%
“…Additionally, COPI, through its subunit α-COP, binds with survival motor neuron protein (SMN), which is deficient in spinal muscular atrophy (SMA) and is involved in its axonal transport [59]. Furthermore, SMA patients show abnormal Golgi apparatus morphology which can be corrected by overexpression of α-COP [60].…”
Section: Discussionmentioning
confidence: 99%